Negative effective mass of a filled carbon nanotube. (December 2017) - Lu, Lu; Ru, C.Q.; Guo, Xingming
Highlights: A simple continuum model is developed for a filled CNT. It is found that a filled CNT can behave like a metamaterial with negative mass. The locally resonant bandgap of a filled CNT is determined. Vibration isolation for the proposed CNT-based metamaterial is examined. Abstract: The present paper shows that a carbon nanotube filled with a mass chain behaves like a metamaterial which exhibits negative effective mass density within a certain range of frequencies. Unlike the known elastic metamaterials proposed in literature which are all based on artificial design of their microstructure, a filled carbon nanotube offers an already fabricated metamaterial which exhibits negative effective mass density and achieves desirable metamaterial dynamic properties even without any artificial design of microstructure. To demonstrate metamaterial dynamic behaviors of such a filled carbon nanotube, a simple continuum model is used to study flexural vibration of a hinged filled carbon nanotube. It is confirmed that the locally resonant bandgap of a filled carbon nanotube is determined by the mass of the inserted mass chain and the van der Waals interaction coefficient between the inserted mass chain and the surrounding carbon nanotube, and the expected metamaterial behavior can be demonstrated by remarkable vibration isolation. Actually, our results show clearly that when the applied excitation frequency is within the bandgap, forced vibration of a filled carbon nanotube is highly restricted to a narrow region around the site of the applied external excitation whose width is only a few times the outer diameter of the carbon nanotube. Graphical abstract: